A BIBLIOMETRIC ANALYSIS OF STUDIES ON KNOWLEDGE LEVELS, AWARENESS, ATTITUDES, ANXIETY LEVELS, AND RISK PERCEPTION REGARDING DENTAL RADIATION AMONG PATIENTS, DENTAL STUDENTS, AND DENTAL HEALTH PROFESSIONALS - Menduh Sercan Kaya (International Journal of Advanced Research, 2026)
The aim of this bibliometric study was to assess the scientific development and thematic structure of the literature on the knowledge, awareness, anxiety, risk perception and radiation protection related to dental radiation among patients, dental students and dental health professionals. Bibliometric analysis was performed on 74 publications obtained from Web of Science Core Collection database by Bibliometrix and Biblioshiny. Analyzes of annual scientific production, co-occurrence, thematic map and thematic evolution were done. Scientific production increased especially from 2017 and reached its maximum in 2025. The analyzes revealed that the literature was organized around patient-oriented risk and anxiety and knowledge, awareness and radiation protection. The Patient theme maintained its continuity over the periods. The results show that the research structure of dental radiation is multidimensional, and it has been developed significantly in the recent years.